The Genus Plagiochila (Dumort.) Dumort. (Marchantiophyta) in Madagascar - (:unkn) unknown (My University, 2022)
Plagiochila (Dumort.) Dumort. is one of the largest liverwort genera of Madagascar. A study of the rich Plagiochila holdings from Madagascar kept in the herbaria of Brussels, Eger and Paris leads to the recognition of 22 species, in six sections. One species, P. vandenberghenii Gradst., sp. nov., is new to science and P. bifaria (Sw.) Lindenb., P. macrostachya Lindenb. (synonym: P. granditexta Steph. syn. nov.) and P. simplex (Sw.) Lindenb., all three from the Neotropics, are recorded for the first time from Africa. Madagascar harbors about half of the African Plagiochilas and three species are endemic, P. fracta Pócs, P. sikorae Steph. and P. vandenberghenii Gradst., sp. nov. The high Plagiochila richness of Madagascar is explained by the large tracts on the island of humid tropical montane forest, being the preferred habitat of the genus. East African and Afro-American taxa prevail and four species, P. bifaria, P. macrostachya, P. simplex and P. stricta Lindenb., have a peri-Afro-American range being absent on the African mainland. A key to the Madagassan species of Plagiochila is provided and each species is described and illustrated, with data on types, synonyms, geographical distribution, habitat and differentiating characters.
Keywords: African Research